Pengetahuan, Sikap dan Kepatuhan Penggunaan Masker oleh Ibu Hamil pada Masa Pandemi CoVid-19 di Kota Denpasar - Ni Made Dwi Purnamayanti; Ni Komang Erny Astiti (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2021)
Corona virus diseases 2019 (CoVid-19) spreads very quickly through droplets or indirectly when touching objects or area exposed to the virus. Since the first cases were announced, the number of cases in Bali has increased rapidly, including among pregnant women. The use of face masks is one of the strategies to prevent transmission. This study aims to analyze the relationship between knowledge, attitudes and compliance with the use of mask by pregnant woman during the CoVid-19 pandemic in Denpasar-Bali. This research is a quantitative observational study with a cross-sectional approach. 97 pregnant women in Denpasar during 2020 were involved in this study. Data were collected using a questionnaire that was filled out online. The results showed that most pregnant women had good knowledge, attitude and compliance regarding the use of masks during the CoVid-19 pandemic (respectively 92,8%, 77,3% and 67,0%). There is no relationship between knowledge and compliance with the use of masks. There is a relationship between attitude and compliance with the use of mask by pregnant women during the CoVid-19 pandemic in Denpasar-Bali.